Autosomal dominant polycystic kidney disease in absence of renal cyst formation illustrates genetic interaction between WT1 and PKD1. Issue 2 (7th May 2020) - Münch, Johannes; Kirschner, Karin M; Schlee, Hendrik; Kraus, Cornelia; Schönauer, Ria; Jin, Wenjun; Le Duc, Diana; Scholz, Holger; Halbritter, Jan
Abstract : Purpose: Autosomal dominant polycystic kidney disease (ADPKD), caused by pathogenic variants of either PKD1 or PKD2, is characterised by wide interfamilial and intrafamilial phenotypic variability. This study aimed to determine the molecular basis of marked clinical variability in ADPKD family members and sought to analyse whether alterations of WT1 (Wilms tumour 1), encoding a regulator of gene expression, may have an impact on renal cyst formation. Methods: ADPKD family members underwent clinical and molecular evaluation. Functionally, Pkd1 mRNA and protein expression upon Wt1 knockdown was evaluated in mouse embryonic kidneys and mesonephric M15 cells. Results: By renal gene panel analysis, we identified two pathogenic variants in an individual with maternal history of ADPKD, however, without cystic kidneys but polycystic liver disease: a known PKD1 missense variant (c.8311G>A, p.Glu2771Lys) and a known de novo WT1 splice site variant (c.1432+4C>T). The latter was previously associated with imbalanced +/−KTS isoform ratio of WT1 . In ex vivo organ cultures from mouse embryonic kidneys, Wt1 knockdown resulted in decreased Pkd1 expression on mRNA and protein level. Conclusion: While the role of WT1 in glomerulopathies has been well established, this report by illustrating genetic interaction with PKD1 proposes WT1 as potential modifier in ADPKD.